Contribuição ao estudo da estabilização e geopolimerização de um solo siltoso da formação Guabirotuba melhorado com pó de vidro e lama de cal - Baldovino, Jair de Jesus Arrieta (2021)
Methodologies for stabilization and geopolymerization of problematic soils with more sustainable materials have gained great attention in recent years. By the addition of these materials to the soil, the consumption of traditional binders such as lime and cement has been reduced. Although the soil-cement and lime-soil blends have been extensively studied, the influence of some parameters such as moisture content, climatic conditions, and porosity/cement index is not well defined for sedimentary silts. Thus, this work presents the technical viability of using powdered glass and lime mud in the stabilization and geopolymerization of a sedimentary silt characteristic of the Guabirotuba Formation in the city of Curitiba/Brazil using residues not used until now for these purposes in local soils. For this purpose, an exhaustive laboratory testing program was carried out to analyze the influence of traditional binders such as cement and lime, and sustainable materials such as glass powder (VM) and lime sludge (LM) residues in improving mechanical strength, durability against wetting-drying or freezing-thawing cycles (in severe climatic conditions) and on the silt microstructure. The experimental program was divided into 4 types of blends: soil-cement, soilcement-VM, soil-lime-VM, and soil-LM-VM. Cement contents between 3-9%, lime/LM content fixed at 5%, and glass powder contents of 5%, 15%, and 30%, all by weight about soil, were used. The mixtures were cured for 7 days and up to 360 days (when appropriate). The results show that there is an increase in the resistance and durability properties of the blends when cement is added. However, the mechanical strength decreases if the mixtures are subjected to freezing-thawing cycles. The opposite can be seen when the mixtures are subjected to drying-wetting cycles, where greater resistance is achieved than that of curing at 23°C in a wet chamber. In the moisture content of 28%, the best mechanical characteristics and durability of the mixes are achieved, regardless of the compaction effort. It has been shown that the porosity/cement ratio is the main variable that controls the mechanical strength, durability, and microstructure of the soil-cement. When cement is not used, the mechanical properties and durability of the improved silt depend on the porosity/binder index. It was shown that it is possible to reduce the consumption of lime or cement by up to 60% in the stabilization of silt using VM and LM residues, with LM being the less suitable due to its slow pozzolanic activity. Besides, compacted blends of soil with different additives and powder residues reach the minimum requirements for strength and durability for use in civil construction. The recommended lime, LM, or cement content is 5% and for VM 10%. Thus, the additions of the studied materials are an adequate technique for the sedimentary soils of the Guabirotuba Formation, since they increase the strength, durability and they are in sufficient quantity to be used in paving applications, mainly.